[PP.02.06] BEETROOT JUICE LOWERS CENTRAL SYSTOLIC BLOOD PRESSURE - A DOUBLE-BLIND CROSSOVER PLACEBO CONTROLLED PILOT TRIAL. (September 2017) - Weber, T.; Waldenberger, G.; Hametner, B.; Wassertheurer, S.; Lirk, G.; Hoeglinger, O.
Abstract : Objective: Dietary inorganic nitrate, originating from beetroot juice, has been shown to lower brachial blood pressure via bioconversion in the enterosalivary circulation. Its effects on central systolic blood pressure (cSBP) are largely unknown. Design and method: 13 healthy young adults received 180 ml Fit Rabbit (FR) juice, containing 11.2 mmol nitrate, or matched placebo (P), at 8.00 AM in a non-fasting state (but free from coffee). Brachial and central BP was measured with a validated, oscillometric system (mobilograph, Stolberg, Germany) and a transfer function, with a measurement interval of 20 minutes during the day, at baseline (B), following FR and P. Primary endpoint was the change in averaged cSBP between the time interval 7.15–8.30 and 09.00–12.30. Results: From the first to the second time interval, central SBP dropped by 3.3 mm Hg (FR) and 0.2 mm Hg (B) and increased by 1.6 mm Hg (P). The changes in the whole group were statistically significant (p = 0.005), as was the change following FR (p = 0.0003) and the difference between B and FR (p = 0.05). In contrast, we observed only minor changes in brachial SBP at B (−0.8 mm Hg) and following FR (−0.2 mm Hg) and P (+1.2 mm Hg) from the first to the second time interval. The BP changes were accompanied by changes in heart rate (HR): + 4.6 (RF), −3.4 (B) and −2.6 (P) beats per minute, respectively. The changes in the whole group were statistically significant (p = 0.02), as was the change following FR (p = 0.02) and the difference between B and FR (p = 0.01). In exploratory analysis, the results were comparable, when alternative time windows for the second interval were chosen (09.-11.00 or 11.00–12.30, respectively). Conclusions: Our results show that the effects of beetroot juice on systolic blood pressure may be more pronounced on central rather than on brachial blood pressure.